Avaliação da frequência, atividade enzimática e sensibilidade a antifúngicos de leveduras do gênero Candida isoladas da cavidade bucal de pacientes portadores do HIV - Menezes, Ralciane de Paula (2014)
The prevalence of Candida spp. as commensal of the oral cavity can reach 70%. However, oral cavity colonization not always culminates in oral candidiasis, however it can be considered a preliminary condition for the development of it. Oral candidiasis is the most common fungal infection among individuals with HIV, due the result of immune deficiency. Considering the importance of this type of infection in HIV-positive, we proposed to carry out this work with the following objectives: determine the frequency of HIV positive individuals colonized by Candida spp., Candida species isolated; determine the main predisposing factors for oral colonization by Candida spp., to relate the microbial load of colonization with the count of lymphocytes TCD4+, viral load and antiretroviral therapy used at the time of collection; determine the sensitivity of isolates of Candida spp. antifungal fluconazole, itraconazole, voriconazole, amphotericin B and nystatin, by the methodology of disk diffusion and search for the exoenzymes proteinases, phospholipases, hemolysin and DNase in isolates of Candida spp. From May to October 2012 saliva samples from HIV patients attended at Clinical Hospital - Federal University of Uberlândia and HIV negative individuals were collected, which were seeded onto plates containing Sabouraud Dextrose Agar and CHROMagar Candida plates and incubated in a bacteriological incubator at 30ºC for 72 hours. The identification of the isolates was done by classical methodology, using chromogenic agar and assimilation of carbon sources and nitrogen, the differentiation between C. dubliniensis and C. albicans was made by PCR. Candida spp. were isolated from 89 of the 147 patients studied, a total of 111 isolates, C. albicans the most common species among the isolates (67.6%). The average colony count was 8.8x10³ CFU/mL. In the control group 51 of the 150 saliva samples were positive for Candida, obtained 57 isolates, of which 77.2% were C. albicans. The average of CFU/mL was 9.8x10². The predisposing factors for oral colonization were use of antibiotics and oral prosthesis and a low CD4 + cells count and high viral load. The combined use of antiretroviral class of reverse transcriptase inhibitors had a greater protective effect on the colonization than the use of these drugs associated with protease inhibitors. The nystatin antifungal, voriconazole and amphotericin B showed the highest number of samples of Candida spp. sensitive in both groups followed by fluconazole and itraconazole. The phospholipase production was observed in 69.3% and 72.6% of the isolates from the group of patients and HIV negative, respectively. The production of haemolysin by isolates of HIV positive and non-positive patients, respectively, was to 98.2% and 96.5%, DNAse was produced by 27% and 21% of the isolates from patients and non-patients of HIV. Finally, with the exception of DNAse, there was no statistically significant difference between isolates from the two study groups in the characters studied.